2013
DOI: 10.1152/ajpheart.00397.2013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute vasodilation on the hemodynamic response to muscle metaboreflex

Abstract: The aim of the present study was to test the contribution of stroke volume (SV) in hemodynamic response to muscle metaboreflex activation in healthy individuals. We hypothesized that an acute decrease in cardiac afterload and preload due to the administration of a vasodilating agent could reduce postexercise muscle ischemia (PEMI)-induced SV response. Ten healthy males (age 33.6 ± 1.3 yr) were enrolled and randomly assigned to the following study protocol: 1) PEMI session, 2) control exercise recovery (CER) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 40 publications
(70 reference statements)
5
42
0
Order By: Relevance
“…The response in this parameter was higher in the CTL than in the OMS group, whereas no difference was present between the two groups with obesity, with the MHO group showing a behavior in the medium between those of the CTL and of the OMS group. The increase in VFR occurring in the CTL and in the MHO group is similar to what has been reported in previous human research with similar experimental settings (13,14,29) and confirms that an increase in diastolic flow takes place during the metaboreflex in normal individuals, probably because of a sympathetic-mediated venous and splanchnic constriction (32,53,54). The lack of VFR response in the OMS group appears to suggest that, in subjects with complicated obesity, certain phenomena likely prevented the normal increase in venous return and cardiac preload.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The response in this parameter was higher in the CTL than in the OMS group, whereas no difference was present between the two groups with obesity, with the MHO group showing a behavior in the medium between those of the CTL and of the OMS group. The increase in VFR occurring in the CTL and in the MHO group is similar to what has been reported in previous human research with similar experimental settings (13,14,29) and confirms that an increase in diastolic flow takes place during the metaboreflex in normal individuals, probably because of a sympathetic-mediated venous and splanchnic constriction (32,53,54). The lack of VFR response in the OMS group appears to suggest that, in subjects with complicated obesity, certain phenomena likely prevented the normal increase in venous return and cardiac preload.…”
Section: Discussionsupporting
confidence: 89%
“…The possibility to modulate SV has been defined crucial in the metaboreflex activation by means of PEMI, since in this setting HR does not normally have an evident response because of the elevated vagal tone, which counteracts the sympathetic activation (25,38). Thus, to increase/or to maintain stable CO values, cardiovascular regulatory mechanisms can only rely on the SV reserve, which can be recruited by enhancing cardiac performance and/or cardiac preload (11,13,29,33). In the present study, the OMS group showed a tendency to decrease SV response during the metaboreflex, whereas normal subjects increased this parameter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the local circulatory occlusion used to trap metabolites that activate metaboreflex prevents venous dilation, which is a major component of metaboreflex activation (10,25). To avoid this obstacle, we chose to use a 1-min 50% MVC handgrip model, which is known to evoke the muscle metaboreflex without increasing HR, SV, or CO.…”
Section: Limitationsmentioning
confidence: 99%